Analisis Unsur 'Tanpa Hak' dalam Delik Kesusilaan UU ITE dalam Kasus Revenge Porn - Hendrikus Nesi; Ramli Umar (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The advancement of digital technology has created new opportunities for cybercrime, including revenge porn the non-consensual distribution of intimate content motivated by revenge. In Indonesia, such cases have surged significantly, predominantly affecting women of productive age, with multidimensional consequences including psychological trauma, social stigmatization, and job loss. This study analyzes the element 'without right' (tanpa hak) in Article 27 paragraph (1) of the Electronic Information and Transactions Law (UU ITE), which is both the core and the main source of legal uncertainty in prosecuting revenge porn cases. Through normative legal research using statute and case approaches, analyzing the Banten High Court Decision No. 96/Pid.Sus/2023/PT BTN, this research finds that the element 'without right' must be interpreted holistically by making a clear distinction between consent to create and consent to distribute. The appellate court decision demonstrates a progressive human rights-based approach, integrating the principle of reasonable expectation of privacy and victimological impacts. However, normative ambiguity continues to create disparities in rulings and disproportionate evidentiary burdens on victims. The research recommends legislative reform through amendment of the UU ITE or enactment of specific legislation on image-based sexual abuse to provide stronger legal certainty and substantive victim protection.